Integration Of Intellectual Intelligence, Emotional Intelligence And Role Stress On Auditor Performance With Spiritual Intelligence And Religiosity As Moderating Variables (Empirical Study at the Inspectorate in Riau Province) - Syafrinadina, Syafrinadina; Joniputra, Joniputra; Syafwandi, Syafwandi; lusiana, lusiana (Cita konsultindo, 2024)
This study aims to obtain empirical evidence of the integration of Intellectual Intelligence, Emotional Intelligence and Role Stress on auditor performance with Spiritual Intelligence and Religiousness as moderating variables at the Inspectorate in Riau Province. The population in this study were all auditors at the Inspectorate in Riau Province. The data analysis model for sample selection was by convenience sampling, so that the total sample filling out the questionnaire for this study was 117 respondents. The data analysis method used Partial Least Squares with WarpPLS 7.0 software to test the integration of the influence of Intellectual Intelligence, Emotional Intelligence and Role Stress on Auditor Performance with Spiritual Intelligence and Religiousness as moderating variables. The results of this study indicate that the Intellectual Intelligence variable has a positive effect on Auditor Performance; The Emotional Intelligence variable has a negative effect on Auditor Performance and the Role Stress variable has a positive and significant effect on Auditor Performance. Spiritual Intelligence moderates the influence of Intellectual Intelligence, Emotional Intelligence and Role Stress on Auditor Performance and Religiousness moderates the influence of Emotional Intelligence and Role Stress on Auditor Performance and does not moderate the influence of Intellectual Intelligence on Auditor Performance.